Perbandingan Model Pembelajaran Problem Based Learning dan Discovery Learning terhadap Hasil Belajar Siswa - Muthmainnah Asmal (Departement of Mathematics Education, 2023)
The purpose of this study was to compare the effectiveness of Discovery Learning learning model and Problem Based Learning learning model on student learning outcomes. This research is a quasi-experimental research conducted on students of class VII SMP Negeri 1 Palopo, which uses two groups of students given different treatments. Experimental group A used Discovery learning model while Experimental group B used Problem Based Learning model. The results showed from data analysis that tvalue 2.03 and ttable 1.99, with testing criterion of Ha accepted if tvalue > ttable. It was concluded that there is a significant difference between posttest learning results in Experimental Group A that uses Discovery learning model and Experimental Group B that uses Problem Based Learning model. According to average values of both classes, it indicates that Discovery Learning model is more effective on students' learning outcomes than Problem Based Learning model.